Effect of Marine and Land Convection on Wet Scavenging of Ozone Precursors Observed During a SEAC4RS Case Study. Issue 5 (23rd February 2023) - Cuchiara, G. C.; Fried, A.; Barth, M. C.; Bela, M. M.; Homeyer, C. R.; Walega, J.; Weibring, P.; Richter, D.; Woods, S.; Beyersdorf, A.; Bui, T. V.; Dean‐Day, J.
Abstract: Convective clouds are important for both the vertical redistribution of tropospheric trace gases and the removal, via microphysical scavenging, of soluble trace gas precursors of ozone. We investigate wet scavenging of formaldehyde (CH2 O), hydrogen peroxide (H2 O2 ), and methyl hydrogen peroxide (CH3 OOH) in quasi‐marine and land convective storms over Texas, USA observed on 18 September 2013 during the 2013 SEAC 4 RS campaign. Cloud‐resolving simulations using the Weather Research and Forecasting model with Chemistry (WRF‐Chem) were performed to understand the effect of entrainment, scavenging efficiency (SE), and ice physics processes on these trace gases with varying solubility. While marine and land convection can have distinctly different microphysical properties, we did not find significant differences in the SEs of CH2 O, H2 O2, or CH3 OOH. The SEs of 44%–53% for CH2 O and 85%–90% for H2 O2 are consistent with our previous studies from SEAC 4 RS and the 2012 DC3 field experiment storms. Using WRF‐Chem simulations, the ice retention factor ( r f ) for CH2 O was determined to be 0.5–0.9, which is higher than found in previous studies. We show that the CH2 O r f is higher in airmass and multicell storms than in severe storms and hypothesize that ice shattering may affect CH2 O r f values. The CH3 OOH SEs (39%–73%) were higher than expected from Henry's Law equilibrium. While recent studies suggest that CH3 OOH measurements have interference due to methane diol, we find that this interference cannot fully explain the higher‐than‐expected CH3 OOH SEs determined here and during DC3, suggesting further research is needed to understand CH3 OOH vertical redistribution. Plain Language Summary: Thunderstorms are important mechanisms for the transport and removal of trace gases in the atmosphere. This study investigates the transport and removal processes of tropospheric ozone trace gas precursors in marine and land convective storms over Texas, USA. Numerical simulations were performed to understand storm processes affecting atmospheric gases with different solubilities. While marine and land storms can have distinctly different storm structure and updraft winds, we did not find significant differences in the amount of gases removed by these storms. The results show that the efficiency of the storm in removing gas from the atmosphere is consistent with our previous findings for moderate to severe storms over the US. In addition, the analysis showed when cloud drops freeze onto ice and snow particles that formaldehyde had more retention in the frozen particle in moderate storms compared to severe storms suggesting that there are many processes affecting this key ozone precursor in deep convection. The more soluble hydrogen peroxide did not show the same ice retention behavior because it is removed by precipitation in the warmer, liquid‐only region of the storm. Key Points: Although marine and land convection have different microphysical properties, there are no relevant differences in the scavenging efficiency WRF‐Chem simulations analysis shows ice retention factor for formaldehyde is higher than found in previous studies Methyl hydrogen peroxide scavenging efficiencies are higher than expected from Henry's Law, even with potential measurement interference